Implications for fisheries management by inclusion of marine ecosystem services - Lars Ravensbeck; Ayoe Hoff; Hans Frost (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
The application of ecosystem based management of the marine resources and focus on ecosystem services will influence the methodologies used for assessing the resources as well as the proposed regulation of the fisheries and other marine resources. The paper makes a review of ecosystem services and ecosystem based fishery management with the purpose of integrating these elements in a bioeconomic model. As a part of the model development, a logistic predator-prey model is examined thoroughly. On this basis, a numerical model is created. The model can include several species at different trophic layers, hence simulation a small food web. The key purpose of the numerical analysis is to develop a practical tool that can assess the management policies when a broader range of ecosystem services, species interactions and externalities are taken into account. The model can include several species at different trophic layers and, hence, simulate a small food web, while at the same time assess the economic effects of fishing on this food web. In general, the analyses indicate that species modelled with interaction may sustain less fishing pressure than if they are modelled without species interaction. Besides interaction, the numerical model assesses how the economic result is affected by the inclusion of ecosystem services. This is done through the damage cost functions, which depends on effort and reduces the net value, and a set of non-market values, which are functions that depend on the stock of the species. The inclusion of these tends to favour reduction in effort levels, in some cases quite significantly. Management policies based on conventional MEY targets may in many cases rather well accommodate the broader range of ecosystem-based policy goals, due to the lower effort levels. The paper shows the shortcomings of conventional qualitative analytical approaches because of the complexities of marine ecosystems. Numerical models also show shortcomings, in particular because specific functional forms are used and data are short in many areas. However, it is shown that much insight can be gained from using such relatively simple models.
Keywords: Q22; Q57; 330; bioeconomics; ecosystem modelling; ecosystem based fisheries management